Tailoring Microstructure of Graphene‐Based Membrane by Controlled Removal of Trapped Water Inspired by the Phase Diagram. (24th February 2014) - Lv, Wei; Li, Zhengjie; Zhou, Guangmin; Shao, Jiao‐Jing; Kong, Debin; Zheng, Xiaoyu; Li, Baohua; Li, Feng; Kang, Feiyu; Yang, Quan‐Hong
<x xml:space="preserve">Abstract</x> As an important form of graphene assembled in macroscale, the graphene‐based membrane attracts much attention due to its easy manipulation and various potential applications. However, tailoring the microstructure of these membranes is hard to achieve and the surface utilization of graphene layers is low. By analyzing the drying process for the wet graphene oxide membrane (GOM), it is found that the trapped water in freshly formed GOM actually provides potential forces to tune its microstructure. According to the phase diagram of pure water, with a reduced pressure, the trapped water boils seriously and then transforms into ice crystal instantaneously around the triple point. This sudden phase change across the triple point provides strong forces to change and fix the microstructure of GOM. In this study, the ordinary evaporation drying process for the wet GOM is replaced with a two‐stage drying process and the tightly layered structure of graphene membrane is turned into an open and grade structure. The obtained membrane shows high surface utilization. Thus, after reduction, the membrane possesses high adsorption capability towards various molecules, especially for heavy oil and lithium polysulfide products in the cathode of Li–S battery. Furthermore, the membrane shows high rate performance as the electrodes for supercapacitors.